2024
DOI: 10.24084/repqj14.289
|View full text |Cite
|
Sign up to set email alerts
|

Selection the optimal technology for electricity generation of 5 MW using a fuzzy multi-criteria decision-making approach

Abstract: Abstract. Today's challenges towards a sustainable energy development in most European nations are crucial and highly complicated. We find the need to choose between several technologies generation, whose task is very laborious. Multiple factors that affect the success of a Renewable Energy (RE) project must be analyzed and taken into account. The evaluation and comparison of possible technologies generation is a multicriteria decision problem because not only economic aspects must be considered but also techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Like the studies by Cánovas-Rodríguez et al [34], Amer and Daim [22], and Buchholz et al [46], air pollution was selected as the most influential subcriterion by the experts (see Table IV), because of the critical conditions of air pollution in Iran in recent years [96]. According to the environmental performance index, Iran ranks 83rd among 138 countries [97], so any technology that improves air pollution is likely to be preferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the studies by Cánovas-Rodríguez et al [34], Amer and Daim [22], and Buchholz et al [46], air pollution was selected as the most influential subcriterion by the experts (see Table IV), because of the critical conditions of air pollution in Iran in recent years [96]. According to the environmental performance index, Iran ranks 83rd among 138 countries [97], so any technology that improves air pollution is likely to be preferred.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that nuclear energy was the best alternative. Cánovas-Rodríguez et al [34] selected the optimal renewable energy technology for electricity generation in Spain, using fuzzy AHP. Land requirement, social acceptance, labor impact, efficiency, resource availability, economic value, and noise proved to be the most important criteria in their study, identifying wind energy as the best alternative for electricity generation.…”
Section: Literature Reviewmentioning
confidence: 99%